2018
DOI: 10.1515/hc-2018-0107
|View full text |Cite
|
Sign up to set email alerts
|

5-Bromo-1-(4-chlorobenzyl)-1H-indole-2-carboxamides as new potent antibacterial agents

Abstract: Ten 5-bromoindole-2-carboxamides were synthesized, characterized and evaluated for antibacterial activity against pathogenic Gram-negative bacteria Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa and Salmonella Typhi using gentamicin and ciprofloxacin as internal standards. Compounds 7a–c, 7g and 7h exhibit high antibacterial activity with a minimum inhibitory concentration (MIC) of 0.35–1.25 μg/mL. Compounds 7a–c exhibit antibacterial activities that are higher than those of the standards agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The antibacterial SAR of quaternization harman analogs 77–78 against S. aureus , MRSA, B. subtilis , B. cereus , and R. solanacearum revealed that the introduction of methoxy at the C‐5 position of indole moiety and trifluoromethyl at para ‐position of the benzyl group was favorable to the activity. [ 155–157 ] Among them, seven hybrids, 77a,b , 78a,b , and 79a–c , with MIC values of 4–16 μg/ml were found to be most active against the tested five pathogens, and the mechanistic study indicated that these hybrids might exert their bactericidal effect by damaging bacterial cell membrane and wall, and disrupting the function of type II topoisomerase. The in vivo antibacterial activity (protective effect) of hybrid 79b was further tested against R. solanacearum on eggplant leaf, and the results demonstrated that this hybrid possessed a good preventative effect against R. solanacearum with a protective efficacy of 81.3%, proving the potential of the quaternization harman agents as new bactericides and antibiotics.…”
Section: Indole–pyridine/pyrimidine Hybridsmentioning
confidence: 99%
“…The antibacterial SAR of quaternization harman analogs 77–78 against S. aureus , MRSA, B. subtilis , B. cereus , and R. solanacearum revealed that the introduction of methoxy at the C‐5 position of indole moiety and trifluoromethyl at para ‐position of the benzyl group was favorable to the activity. [ 155–157 ] Among them, seven hybrids, 77a,b , 78a,b , and 79a–c , with MIC values of 4–16 μg/ml were found to be most active against the tested five pathogens, and the mechanistic study indicated that these hybrids might exert their bactericidal effect by damaging bacterial cell membrane and wall, and disrupting the function of type II topoisomerase. The in vivo antibacterial activity (protective effect) of hybrid 79b was further tested against R. solanacearum on eggplant leaf, and the results demonstrated that this hybrid possessed a good preventative effect against R. solanacearum with a protective efficacy of 81.3%, proving the potential of the quaternization harman agents as new bactericides and antibiotics.…”
Section: Indole–pyridine/pyrimidine Hybridsmentioning
confidence: 99%
“…The broad spectrum of applications of the indole justifies it being addressed as the "Lord of the Ring". 10 In particular, indole-2-carboxamide scaffolds are known to have significant biological activity such as antitumor, [11][12][13] anti-infiammatory, [14][15][16] antitubercular, [17][18][19] antibacterial [20][21][22] and antifungal [23][24][25][26] (Figure 1). A possible anti-tumor activity is described through growth factor inhibition for kinase tyrosine protein receptors (PTKs), which are found over-expressed in cancer cells.…”
Section: Introductionmentioning
confidence: 99%